A comparison of a modified sequential oral sensory approach to an applied behavior‐analytic approach in the treatment of food selectivity in children with autism spectrum disorder. Issue 3 (23rd July 2016) - Peterson, Kathryn M.; Piazza, Cathleen C.; Volkert, Valerie M.
Abstract : Treatments of pediatric feeding disorders based on applied behavior analysis (ABA) have the most empirical support in the research literature (Volkert & Piazza, 2012); however, professionals often recommend, and caregivers often use, treatments that have limited empirical support. In the current investigation, we compared a modified sequential oral sensory approach (M‐SOS; Benson, Parke, Gannon, & Muñoz, 2013) to an ABA approach for the treatment of the food selectivity of 6 children with autism. We randomly assigned 3 children to ABA and 3 children to M‐SOS and compared the effects of treatment in a multiple baseline design across novel, healthy target foods. We used a multielement design to assess treatment generalization. Consumption of target foods increased for children who received ABA, but not for children who received M‐SOS. We subsequently implemented ABA with the children for whom M‐SOS was not effective and observed a potential treatment generalization effect during ABA when M‐SOS preceded ABA.